Corn crop development (Zea mays L.): literature review/Desenvolvimento da cultura do milho (Zea mays L.): revisão de literatura - Luiz Eduardo Bezerra Silva; José Crisólogo de Sales Silva; Willian Cleisson Lopes de Souza; Luan Lucas Cardoso Lima; Rafael Lima Vieira dos Santos (Universidade Estadual de Alagoas, 2020)
Maize is a plant belonging to the grasses family, or Poaceae, possessingthe second place as the most produced cereal in the country in the year 2017. In this context, through the realization of this review, it was objected to highlight general and peculiar characteristics about maize cultivation. Bringing, in such a way, moreknowledge to the rural and urban population about the potential of culture in the country. In the development of this study, researches of bibliographic nature were conducted, based on the databases of Scielo, Capes and Google scholar, published between the years 2010 to 2018. In the Constitution of this research, we used 44 national articles, 02 International articles, 01 monograph, 02 dissertations, 02 Theses, 01 folder and 02 newsletters. Through the development of this work it was possible to gather important characteristics for the culture, whether they are more general characteristics, popularly disseminated among farmers, as the most peculiar, but of fundamental importance to the Culture development. Thus, it was possible to gather in one work, themes that can help in the development of maize cultivation, increasing the productivity and viability of the crop. It can be concluded that maize constitutes a culture of paramount importance in Brazil and tendsto grow even more.